2024
DOI: 10.3389/fnagi.2023.1280324
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of combined vibratory and plantar stimulation while seated influences plantar pressure and spatiotemporal gait measures in individuals with Parkinson’s disease exhibiting freezing of gait

Warongporn Phuenpathom,
Pattamon Panyakaew,
Peerapon Vateekul
et al.

Abstract: IntroductionCombined plantar pressure and vibratory stimulation has been shown to decrease freezing of gait (FOG) episodes and improve spatiotemporal gait parameters compared to single stimulation in Parkinson’s disease (PD) patients with FOG. However, the effect of combined plantar stimulations on plantar pressure analysis has never been explored.MethodsForty PD patients with frequent FOG were allocated to either FOG shoes embedded with a 100 Hz vibratory stimulation at the Achilles tendons and a soft thicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The present study demonstrated that self-treatment using acupressure with silicone pads to stimulate designated plantar acupoints could effectively alleviate FOG during ON-state by increasing stride length, gait velocity, and cadence and decreasing the number of FOG episodes, FOG duration, and %FOG, which is consistent with previously reported findings using other mechanical stimuli of the designated plantar regions [11] , [13] , [14] , [15] , [16] , [17] . The treatment in which patients repeatedly leaned their seated body weight forward to stimulate acupoints at the head of the big toe and the first metatarsal bone, as targeted by silicone pads placed under the plantar surface, was easy for the patients to perform and can be considered an option for self-treatment outside clinical settings for mildly affected PD patients with ON-FOG.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study demonstrated that self-treatment using acupressure with silicone pads to stimulate designated plantar acupoints could effectively alleviate FOG during ON-state by increasing stride length, gait velocity, and cadence and decreasing the number of FOG episodes, FOG duration, and %FOG, which is consistent with previously reported findings using other mechanical stimuli of the designated plantar regions [11] , [13] , [14] , [15] , [16] , [17] . The treatment in which patients repeatedly leaned their seated body weight forward to stimulate acupoints at the head of the big toe and the first metatarsal bone, as targeted by silicone pads placed under the plantar surface, was easy for the patients to perform and can be considered an option for self-treatment outside clinical settings for mildly affected PD patients with ON-FOG.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesised that deep acupressure with silicone pads targeting the acupoint locations with the highest sensitivity threshold for vibratory and touch pressure might improve peripheral inputs from mechanoreceptors in the regions with sensory deficits [10] better than widely distributed pressure in the plantar region. This improvement may result from pressure stimulus at the designated acupoints in the plantar region, which may sensitise Golgi tendon organs and spindle cells in the tibialis anterior muscle and contribute to dorsiflexion, augmenting heel strike when initiating gait, attributed to impaired anticipatory postural adjustment (APA) [4] , [12] , [13] , [14] , [15] , [16] , [17] , [27] . Moreover, pressure stimulus at the big toe is also related to the push-off while initiating gait, resulting in alleviated FOG [13] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations